Reproductive strategies and gonadal characteristics of indonesian green mussel Perna viridis in Banyuurip Bay: environmental and seasonal influences - Farikhah Farikhah; Triana Retno Palupi; Dedi Fazriansyah Putra; Hany Handajani (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
This study aimed to examine the gonadal characteristics and reproductive strategies of the green mussel Perna viridis in Banyuurip Bay, Java Sea, Gresik Regency, Indonesia, with a focus on oocyte size, gonad morphology, and seasonal variations in reproductive activities. Micromorphological and field observations analysis revealed that the gonad, the site of gametogenesis in female mussels, is characterized by an orange colour. In contrast, in males, it is creamy white. During gametogenesis, the diameter of the oocyte increases from 0.28 to 0.60 μm at the oogonia stage and to 1.17 to 3.19 μm when it becomes a vitellogenic oocyte. Significant daily and seasonal variations are observed, which may contribute to high environmental pressure on the population. The green mussel population continues to grow despite ecological disturbances, including food scarcity and high levels of pollution, which are exerting pressure on the population. The significantly smaller oocyte size compared to other populations was identified as a potential adaptation to these challenges. These findings underscore the importance of understanding reproductive strategies to support sustainable mussel cultivation and effective management, particularly in areas characterized by fluctuating environmental conditions.